A HISTORICAL ANALYSIS OF CHANGING STATUS OF WOMEN IN KASHMIR: CHALLENGES AND FUTURE PROSPECTS - Mr. Muneer Ahmad Dar; Dr. V. B. Lamb (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
Abstract The changing status of women is often assessed based on their roles and positions in social, political, and economic spheres, reflecting gender differentiation in status. The core of gender inequality lies in the unequal access to material and social resources between the sexes (Bhagat, 1990). The status of women in Kashmir has evolved over time, spanning from ancient periods to the modern age. This study aims to review the evolving status of women in the modern era.